Rediscovery and amended description of Psychotria palimlimensis (Rubiaceae): a rare species found only in Ilocos Norte, Philippines. (23rd July 2021) - Batuyong, Mae Ann R.; Calaramo, Michael A.; Alejandro, Grecebio Jonathan D.
Abstract : Recent exploration on the northern Cordillera Mountain Range of Ilocos Norte, Philippines, resulted in the rediscovery of Psychotria palimlimensis Sohmer & A.P. Davis. This is an endemic Psychotria species first collected by Ramos in 1918 and identified as P. subalpina . However, the diagnosis of Sohmer and A.P. Davis in 2007 proposed it as a new species based on herbarium materials, and no further recollection was made to date since its last collection in 1953. Therefore, an amended taxonomic description of P. palimlimensis is proposed with color photographs, additional records on the distribution and morphological comparison with its allied species. The current conservation status is also provided.